Remote teaching during COVID-19: Implications from a national survey of language educators. (April 2021) - Moser, Kelly M.; Wei, Tianlan; Brenner, Devon
Abstract: To mitigate transmission of COVID-19, rapid changes in instructional delivery moved from in-person to remote instruction. Although literature from before the crisis suggests that online language learners fare at least as well as their face-to-face counterparts, the abrupt shift from face-to-face contexts to remote learning is fundamentally different from planned online learning . Understanding the nature of this shift can inform future online and remote teaching. This national survey study was guided by research questions that explore any substantive change in the practices and perceptions of PreK-12 and post-secondary language teachers' instruction during COVID-19. It explores any change as related to classroom setting (PreK-12 vs post-secondary) and prior experience with distance education. Data suggest that few language educators reported experiences with or positive perceptions toward teaching online before COVID-19. However, they made numerous adjustments to their typical procedures/policies and expectations while engaged in remote teaching. Educators expressed concerns about student outcomes. PreK-12 teachers and those without prior experience with online teaching were least confident that instructional goals were met despite having reported well-designed courses. Implications for effective remote language teaching are presented for consideration.